Infectious madness : the surprising science of how we "catch" mental illness - Washington, Harriet A. (Little, Brown and Company, 2015)
"Is it possible to catch autism or OCD the same way we catch the flu? Can a child's contact with cat litter lead to schizophrenia? In her eye-opening new book, National Book Critics Circle Award-winning author Harriet Washington reveals that we can in fact "catch" mental illness. In Infectious Madness, Washington presents the new germ theory, which posits not only that many instances of Alzheimer's, OCD, and schizophrenia are caused by viruses, prions, and bacteria, but also that with antibiotics, vaccinations, and other strategies, these cases can be easily prevented or treated. Packed with cutting-edge research and tantalizing mysteries, Infectious Madness is rich in science, characters, and practical advice on how to protect yourself and your children from exposure to infectious threats that could sabotage your mental and physical health"--